Rodent-borne parasites in Qatar: A possible risk at the human-animal-ecosystem interface - Md Mazharul, Islam (2024)
Rodents are known reservoirs for a diverse group of zoonotic pathogens that can pose a threat to human health. Therefore, it is crucial to investigate these pathogens to institute prevention and control measures. To achieve this, the current study was conducted to investigate the frequency of different parasites in commensal rodents in Qatar. A total of 148 rodents, including Rattus norvegicus, Rattus rattus, and Mus musculus were captured using traps placed in different habitats such as agricultural and livestock farms, residential areas, and other localities. Blood, feces, ectoparasite, and visceral organs were collected for gross, microscopic, immunological, and molecular analysis. The study identified 10 different parasites, including Capillaria annulosa, Eimeria spp., Giardia spp., Hymenolepis diminuta, Mastophorus muris, Ornithonyssus bacoti, Taenia taeniaeformis, Toxoplasma gondii, Trypanosoma lewisi, and Xenopsylla astia. Overall, 62.2% of the rodents tested positive for at least one parasite species. Helminths were found to be the most prevalent parasites (46.0%), followed by ectoparasites (31.8%), and protozoa (10.1%). However, individually, X. astia was the most prevalent (31.8%), whereas C. annulosa was the least common (0.7%). The prevalence of X. astia and H. diminuta significantly differed between habitats (p < 0.05). The sequence analysis of Hymenolepis spp. was closely related to the previously reported H. diminuta in Iran, China, and Mexico. In conclusion, the study identified a diverse range of rodent-borne parasites that are important to public health, with most of them being recorded for the first time among commensal rodents in Qatar.